CLINICAL PROFILE OF PATIENTS WITH UNDESCENDED TESTIS IN TERTIARY HOSPITAL - Rachma Fitri Sulistyanti; Besut Daryanto; Pradana Nurhadi (Jurnal Urologi Indonesia)
Objective: The objective of this study is to present the clinical profile of patients with UDT in tertiary hospital. Material & Methods: This study used a descriptive retrospective approached with approved ethical number 400/019/K.3/102.7/2024. Collecting identification was done by tracing UDT case-patient documents from January 2015 to December 2023. The characteristics observed were age, location of UDT, unpalpable or palpable, patient's address, and antenatal care examination. Results: